KRITIS DITINJAU DARI DISPOSISI KEMAMPUAN BERPIKIR KRITIS DITINJAU DARI DISPOSISI MATEMATIS SISWA SMP NEGERI 3 PURWOKERTO - Fita Ristanti (AlphaMath : Journal of Mathematics Education, 2017)
This research aimed to describe critical thinking ability at students of SMP Negeri 3Purwokerto viewed from mathematical disposition. The subject was the students of class VIIIE. Purposive sampling was used as sampling methods. The subject was taken from eachmathematical disposition category namely high, fair and low. The questionnaire, test,interview, and documentation were used for collecting data. Triangulation technique was usedfor validation test. 1) Students with high mathematical disposition categpry had already filled2 out 3 critical thinking indicators that they were able to compose information systematicallyand prove a truth for a problem. However, they failled on giving argument accurately becauseof their inaccuracies at the end the process. 2) Students with fair mathematical dispositioncategory had already filled the indicator of being able to prove a truth for a problem.3) Students with a low mathematical disposition category had not filled all the criticalthinking indicators yet.KEY WORDS: Critical thiking ability, Mathematical disposition